ChemInform Abstract: A Systematic Approach to Diverse, Lead‐Like Scaffolds from α, α‐Disubstituted Amino Acids. Issue 48 (December 2015) - Foley, Daniel J.; Doveston, Richard G.; Churcher, Ian; Nelson, Adam; Marsden, Stephen P.
Abstract: Four amino acid‐derived building blocks are converted into 22 scaffolds, e.g. azides (III) and (XIV), hydantoins (IV), lactams (VI), tetrahydropyridines (IX), and azepanes (XII).